Fracture Fixation in an Unstable Scaphoid Fracture Model: A Biomechanical Comparison of Double Screw Osteosynthesis With Two Common Bone Graft and Fixation Techniques - Surke, Carsten; Del Rosario, Phoebe A; Huntington, Lachlan S; Ek, Eugene T H; Tham, Stephen K; Ackland, David (The Journal of hand surgery (American ed.), 2025)
Rotational instability is an important contributor to nonunion in scaphoid waist fractures treated with a single compression screw. Double screw osteosynthesis demonstrates enhanced resistance to bending loads in unstable fracture models. This method may also provide better rotational strength, improving the construct's resistance to higher loads. This study aimed to evaluate and compare the torsional and cantilever bending strength of double screw fixation against single screw repairs combined with a strut graft and a wedge graft. Volar open wedge osteotomies were performed on 48 cadaveric scaphoids using customized surgical guides. Each specimen was randomly allocated to one of three treatment groups: (1) a single screw with strut graft, (2) a single screw with wedge graft, and (3) double screw fixation. Constructs underwent bending or torsion testing to 10° rotation using a mechanical testing apparatus. Stiffness, maximum torsional force, and load to 2.0 mm displacement were measured. Double screw fixation constructs required more force to achieve 2.0 mm displacement during bending than single screw fixation constructs (mean difference: 78.3 N). The double screw group exhibited considerably greater maximum torque in the screw tightening direction than both the single screw and strut group (mean difference: 65.6 N·mm) and the single screw and wedge group (mean difference: 60.6 N·mm). Furthermore, it also demonstrated considerably higher maximum stiffness in the screw tightening direction compared to the single screw and strut group (mean difference: 4.8 N·mm/deg) and the single screw and wedge group (mean difference: 9.3 N·mm/deg). Double screw fixation for scaphoid waist fractures with volar bone loss yields greater rotational and bending stability than single screw and strut or single screw and wedge graft constructs. The superior stability provided by the double screw osteosynthesis could eliminate the need for time-consuming corticocancellous bone grafting.